Barriers to financial access of disabled people to health services in rural areas: A case study of Iran - Lida Shams; Taha Nasiri; Tahere Darvish; Sayyed-Morteza Hosseini-Shokouh; Mohammad Meskarpour Amiri (Journal of Education and Health Promotion, 2024)
BACKGROUND: People with disabilities (PWDs) account for a significant percentage of the world’s population, with a higher prevalence in less developed countries. Access to healthcare services is the main component of health systems performance, with lower access for PWDs living in rural areas. The current study aimed to investigate PWD’s access to healthcare services in rural areas of Iran and, secondly, factors that contribute to this issue. MATERIALS AND METHODS: Following a cross-sectional design, the current descriptive-analytical study is performed in the north of Iran. Using the quota sampling technique, 471 PWDs were recruited. Data were collected using a valid and reliable questionnaire, covering three dimensions of access, by face-to-face interview. Data analysis was administered using central tendency indicators and multiple regression by SPSS version 17. Statistical significance was considered when the P value <0.05. RESULTS: The mean score of PWD’s access to healthcare services for dimensions of utilization, availability, and affordability was 8.91 (±6.86), 14.54 (±2.3), and 51.91 (±8.78), indicating very low, low, and moderate levels of access. All three regression models were significant (P < 0.05), and variables of gender, age, marital status, education level, residence status, the income of the household head, receiving financial aid, and house area showed a significant effect (P < 0.05). CONCLUSION: This study demonstrated the seriousness of paying attention to PWD’s financial access to healthcare services, particularly in rural areas of Iran. Hence, policymakers should better focus on this problem, mainly regarding accessibility and utilization and factors that result in inequalities.